Parameters affecting lightning backflash over pattern at 132kV double circuit transmission lines - Talib, D.N.A.; Bakar, A.H.A.; Mokhlis, Hazlie (2012)
In this paper, an analysis study on parameters which affecting the backflash over pattern cause by lightning is done. A 132kV double circuit transmission line is modeled using ElectroMagnetic Transient Program EMTP software for backflash over simulation. A vertically configured double circuit transmission line can be modeled into several parts: towers, insulators, phase conductors, ground wire and tower footing resistance. The backflash over pattern is simulating by model the lightning current that hit the ground wire at the aim tower. The parameters that include in this study are the values of front, peak and tail of lightning current, striking distance and lastly the tower ground system. The pattern can also be analysis by taking into account the position of the phase conductors on the double circuit transmission tower.